Analisis Pengukuran Kinerja Berbasis Konsep Vfm (Studi Kasus Badan Pengelolaan Keuangan Kabupaten Aceh Singkil) - Sari, Dewi Puspita; Sartika, Dewi (Universitas Teuku Umar, 2024)
This study analyzes the performance of the Aceh Singkil Regency Financial Management Agency from 2020 to 2022 using the value-for-money concept, which includes economy, efficiency, and effectiveness. By examining financial statements, specifically the Budget Realization Report (LRA) and Government Agency Performance Report (LAKIP), and employing time series data, this quantitative research reveals that the agency achieved a very good rating. The economic ratio averaged 95.65% (economical), the efficiency ratio 92% (efficient), and the effectiveness ratio 103% (effective), demonstrating that the agency has successfully applied value-for-money principles in budget management. Initially focused on inputs, outputs, and outcomes, the agency has since expanded its approach, achieving strong results in managing its programs and budget effectively.